Adherence to life’s essential 8 and progression trajectory of cardiometabolic multimorbidity: a prospective cohort study - Hao Bai; Chengmiao Qiu; Miaomiao Fan; Yang Zhong; Xiaolin Yin; Tongchao Zhang; Hao Chen; Xiaorong Yang; Yuan Zhang; Shujuan Lin; Liyong Chen; Ming Lv (Nutrition & Metabolism)
Abstract Background The Life’s Essential 8 (LE8) score, developed by the American Heart Association to evaluate cardiovascular health (CVH), was recently updated. Few studies have explored its effect on the incidence, progression, and prognosis of cardiometabolic multimorbidity (CMM). This study examines the association between the LE8 and the progress of CMM. Methods This prospective cohort study included 264,597 participants from the UK Biobank. CMM was defined as the presence of at least two of the three cardiometabolic diseases (CMDs): type 2 diabetes (T2D), stroke, and ischemic heart disease (IHD). Multi-state models were employed to investigate the relationship between the LE8 score and its subscales with risk of transitions from healthy to the onset of first cardiometabolic diseases (FCMD), followed by progression to CMM and to death. Results Over a median follow-up of 13.94 years, 33,868 individuals developed at least one CMD, 4282 were diagnosed with CMM, and 4955 died. The results indicated that for each 1-SD increase in the LE8 score, a notable reduction was observed in the rate of progression from baseline to FCMD, baseline to death, and FCMD to CMM, with hazard ratios (HRs) of 0.64 (95% CI: 0.63, 0.65), 0.83 (95% CI: 0.81, 0.85), and 0.80 (95% CI: 0.78, 0.83), respectively. However, no correlation was found between the LE8 score and the transition from FCMD or CMM to death. By contrast, per 1-SD increment in the behavior scale score was associated with decreased risk of transition from FCMD to death (HR: 0.93; 95% CI: 0.90, 0.95) and from CMM to death (HR: 0.89; 95% CI: 0.88, 0.95), while per 1-SD increment in the biological scale score was associated with increased risk of transition from FCMD to death (HR: 1.10; 95% CI: 1.07, 1.14), and from CMM to death (HR: 1.22; 95% CI: 1.15, 1.29). Conclusion The LE8 defined CVH influences the progression from a healthy state to FCMD, CMM, and death, highlighting the importance of improving CVH as a comprehensive approach for preventing CMM.